LEGAL PROTECTION FOR DOCTORS IN THE CHALLENGE OF MEDICAL REFERRAL FOR PRISONERS AT CLASS II B LUBUK PAKAM PRISON INSTITUTION - Emmeninta Florensia Surbakti; Muhammad Arif Sahlepi; Rahmayanti, Rahmayanti (International Journal of Synergy in Law, Criminal, and Justice, 2025)
There is a significant misalignment between existing regulations and practices on the ground, which not only hinders timely medical services but also places doctors at high legal risk. Law Number 22 of 2022 concerning Corrections and Government Regulation Number 32 of 1999 provide a legal framework for prisoner health services but their implementation often experiences obstacles. The research method used is empirical with data collection through direct observation and in-depth interviews with prisoners, doctors, and administrative staff. This study aims to understand in real terms how health services are provided and identify gaps between policy and daily practice. The study found that long and complicated bureaucratic processes and lack of adequate facilities are major obstacles to effective health care provision in prisons. Doctors are often reluctant to immediately refer prisoners to outside facilities without the approval of the prison warden, even if the patient’s medical condition requires immediate treatment. Based on these findings, the study recommends bureaucratic reforms to streamline the medical referral process, regular training for prison wardens and administrative staff, and stronger legal protection for doctors. The study underscores the importance of closer integration of prison health services with the national health system and strengthening oversight mechanisms to ensure effective and humane implementation of regulations.